A high-conductivity core-shell carbon rod and preparation method thereof
Through the low-temperature rapid dehydration and carbonization process, bamboo raw materials are prepared into high-conductive core-shell carbon rods, solving the traditional preparation problem of high temperature and high energy consumption, and achieving efficient and energy-saving carbon rod preparation.
Patent Information
- Application Number
- CN202211088223.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-07
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2042-09-07
AI Technical Summary
The prior art requires high-temperature heat treatment and cumbersome forming processes when preparing highly conductive carbon rods, resulting in huge energy consumption, long time and difficult to meet the cost control requirements of large-scale applications.
By immersing bamboo raw materials into the dehydrated carbonization reaction liquid, controlling the concentration, reaction time and bamboo size of the reaction liquid, achieving a fast carbonization process at low temperatures and forming a highly conductive core-shell structure carbon rod.
The rapid preparation of highly conductive core-shell carbon rods is achieved at low temperatures (to 95°C), reducing energy consumption by about 80% in traditional technology and shortening man-hours by about 60%. The carbon rods have high conductivity and high toughness.
Smart Images

Figure CN115498184B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of carbon material preparation, and particularly relates to a high-conductivity core-shell carbon rod and a preparation method thereof. Background Art
[0002] Biomass-derived carbon rod materials are carbon-rich solid materials produced by high-temperature thermochemical conversion under oxygen-deficient or oxygen-free conditions. They have attracted great attention in the fields of filtration, adsorption, sensing and batteries due to their wide range of raw material sources, renewable, high porosity and conductivity. More importantly, biomass provides an ideal raw material for the preparation of carbon materials with controllable morphology and excellent performance due to its natural hierarchical structure and diverse composition. However, as mentioned above, the preparation process of biomass carbon rods requires very high-temperature thermal conversion, and requires tedious processes such as grinding and reshaping, which consumes huge amounts of energy and time. Therefore, there is an urgent need to develop a low-temperature and rapid large-scale technology for the preparation of highly conductive carbon rods.
[0003] At present, the preparation of highly conductive carbon rods mostly requires high-temperature heat treatment and a series of secondary molding processes. A Chinese patent with patent number CN 114420883A discloses a method of using purified terephthalic acid (PTA) as a raw material, using isopropyl alcohol and tannic acid as adhesives to make PTA rods, and then obtaining macroporous layered carbon rods through high-temperature heat treatment.
[0004] The Chinese patent with patent number CN114420883A discloses a method for preparing a macroporous layered carbon rod, comprising: mixing isopropanol or anhydrous ethanol with deionized water at room temperature, stirring for 4-8 minutes, then adding ammonia water, stirring for 50-80 minutes, then adding tannic acid, stirring for 25-35 hours, finally collecting the solid by centrifugation, washing and drying, and obtaining a precursor PTA rod; heat-treating the precursor PTA rod to obtain a sodium ion battery negative electrode material PTA macroporous layered carbon rod. The sodium ion battery negative electrode material PTA macroporous layered carbon rod prepared by the present invention has a regular material structure, a layered structure and pores, and good stability. As a sodium ion battery negative electrode material, it has a high specific capacity and good rate performance.
[0005] However, the carbon source of the carbon rod disclosed in the above patent is toxic PTA organic matter, which needs to be subjected to complex molding treatment and then carbonized at a high carbonization temperature. This process consumes a lot of energy and produces a lot of heat, which cannot meet the current development requirements of energy conservation and emission reduction.
[0006] On the other hand, most of the current biomass carbonization strategies still rely on high-temperature carbonization methods at around 800°C and cumbersome molding processes to thermally convert biomass into carbon and then manufacture it into carbon rods. This process consumes a lot of energy, takes a long time to prepare, and requires the assistance of multiple equipment, which cannot meet the cost control requirements of large-scale applications.
[0007] In view of this, the use of sustainable biomass as a carbon source and the low-temperature and rapid preparation technology of highly conductive carbon rods are issues that need to be addressed at present. Summary of the invention
[0008] The present invention provides a method for preparing a high-conductivity core-shell carbon rod. The method can prepare the high-conductivity core-shell carbon rod quickly at low temperature. The prepared high-conductivity core-shell carbon rod has high conductivity and high toughness.
[0009] A method for preparing a highly conductive core-shell carbon rod, comprising:
[0010] (1) cutting and polishing bamboo to obtain bamboo raw materials with a diameter of 0.5-5 cm and a length of 10-30 cm;
[0011] (2) 5-20 bamboo raw materials are bundled and fixed, and the lower part of the fixed bamboo raw materials is immersed in 20-400 mL of dehydrated carbonization reaction liquid, the concentration of the reaction liquid is 10-98%, and the temperature is kept for 0.5-4 hours to obtain a core-shell carbon rod;
[0012] (3) The core-shell carbon rod is immersed in deionized water for at least 2 hours and then air-dried, and the uncarbonized portion of the air-dried core-shell carbon rod is cut off to obtain a highly conductive core-shell carbon rod.
[0013] The present invention immerses the lower half of the bundled bamboo into a dehydrated carbonization reaction liquid, and controls the concentration of the reaction liquid, the reaction time and the size of the bamboo raw material so that the outer side of the bamboo material is carbonized while the inner side remains bamboo fiber, thereby forming a core-shell structured carbon rod with high conductivity, good toughness and small volume shrinkage.
[0014] If the diameter of the bamboo raw material is low, the inside of the core-shell carbon rod will also be carbonized, resulting in poor toughness. If the diameter is large, the outer carbonized layer will be thinner, the conductivity will be poor, and it will be easy to crack. If the concentration of the reaction liquid is too high, the carbonization speed will be too fast to form a core-shell structure. Since the carbonized layer formed at the beginning will play a certain role in hindering dehydration, but if the insulation time is too long, dehydration will continue, resulting in over-carbonization, and the formed core-shell structure has poor flexibility.
[0015] The dehydration and carbonization reaction liquid was used to carry out two simultaneous chemical reaction processes of dehydration and carbonization on the cylindrical bamboo raw materials in the solution. x (H2O)y ] is composed of three elements: carbon (C), hydrogen (H), and oxygen (O). The ratio of H to O in the molecule is usually 2:1, which is the same as the ratio in water molecules (H2O). The clever thing is that the dehydration carbonization process removes hydrogen atoms (H) and oxygen atoms (O) from the raw materials in a ratio of 2:1, which is equivalent to removing the target amount of (H2O) y molecules, the rest are mainly carbon atoms (C x ), achieving chemical carbonization. The chemical reaction activation energy required for this process is low, so the reaction start-up temperature is low, the reaction progresses rapidly, the carbonization depth is controllable, and there is no carbon emission.
[0016] In step (1):
[0017] The bamboo is 3-5 years old. The bamboo of suitable age has a good multi-layer structure, and the outer side is relatively dense. During the dehydration carbonization process, a good outer layer carbonization can be formed, and the inner layer is still a fibrous structure.
[0018] The method for preparing the bamboo raw material comprises:
[0019] The bamboo is cut into bamboo slices, the bamboo slices are air-dried for 5-10 days to form yellow-brown bamboo slices, the yellow-brown bamboo slices are cut into bamboo sticks, and the bamboo sticks are polished to obtain bamboo raw materials.
[0020] The bamboo is one of arrow bamboo, spotted bamboo, water bamboo, nan bamboo, arhat bamboo and phoenix tail bamboo.
[0021] In step (2):
[0022] The fixed bamboo raw material is immersed in the dehydrated carbonization reaction liquid for a length of 1-10 cm.
[0023] The reaction liquid is one or more of phosphorus pentoxide (P2O5) solution, phosphoric acid (H3PO4) solution, fuming sulfuric acid (H2S2O7) solution, sodium nitrate (NaNO3), hydrochloric acid (HCl), and citric acid (C6H8O7).
[0024] The insulation temperature is 55-95° C. If the temperature is too low, the reaction liquid cannot be carbonized, and if the temperature is too high, the water vapor bubbles formed will attack the outer carbonized layer, resulting in poor mechanical properties of the carbonized layer, and the concentration of the reaction liquid increases due to water evaporation, which accelerates the carbonization process.
[0025] In step (3):
[0026] The volume of the deionized water is 200-3000 mL, and the soaking time is 2-12 hours. The reaction liquid inside the core-shell carbon rod is exchanged with deionized water to avoid further carbonization of the reaction liquid inside the carbon rod and reduce the flexibility of the carbon rod.
[0027] The present invention uses the abundant and sustainable bamboo biomass in nature as a carbon source to replace some synthetic organic carbon sources, and uses a dehydration carbonization strategy to convert the carbohydrates in the bamboo raw materials [C x (H2O) y ] Hydrogen atoms (H) and oxygen atoms (O) are removed in a ratio of 2:1, and the remaining carbon atoms (C x ), thereby achieving chemical carbonization and quickly obtaining highly conductive core-shell carbon rods. Compared with the traditional carbon rod preparation process: ① No artificially synthesized organic matter and adhesives are required as auxiliary, which increases the added value of natural bamboo biomass; ② It avoids the high energy consumption conditions of high-temperature thermal carbonization, and does not require the use of large-scale industrial high-temperature equipment, which significantly reduces energy consumption and production and construction costs; ③ This preparation process is formed in one step, and the thickness of the carbonized shell is controllable, which avoids the manpower, equipment and time consumption of secondary forming processes such as crushing and pressing in the traditional carbon rod production process. The entire process has opened up a new idea for the production of new carbon rod materials, which meets the requirements of sustainable development and the development goals of green chemistry. It is an ideal negative carbon chemistry strategy for highly conductive core-shell carbon rods.
[0028] The present invention also provides a high-conductivity core-shell carbon rod prepared by the preparation method of the high-conductivity core-shell carbon rod. The interior of the high-conductivity core-shell carbon rod is a bamboo structure, the outer shell is carbon, the carbon content is more than 80%, and the thickness of the outer shell is 40%-65% of the diameter of the high-conductivity core-shell carbon rod.
[0029] The resistivity of the highly conductive core-shell carbon rod is 50-400Ω / cm.
[0030] Compared with the prior art, the present invention has the following excellent effects:
[0031] (1) The present invention obtains a highly conductive core-shell carbon rod by immersing the lower part of the bamboo raw material in a dehydrated carbonization reaction liquid and controlling the concentration of the dehydrated carbonization reaction liquid, the reaction temperature and the insulation time, and the size of the bamboo raw material. The preparation method significantly reduces the biomass carbonization reaction temperature of the traditional technology from about 800°C to below 95°C, the shrinkage rate of the raw material is less than 10%, the preparation process temperature is low and fast, and the energy consumption of the same grade of carbon rod production is reduced by about 80%, and the working hours of the whole process are reduced by about 60%.
[0032] (2) The carbon shell thickness of the highly conductive core-shell carbon rod prepared by the present invention is controllable and adjustable, the carbonization quality is high and the structure matches the natural plant structure. The one-step molding process obtains high conductivity, the resistivity is 50-400Ω / cm and the Young's modulus is as high as 52.4GPa. The two-layer structure includes a highly conductive carbon shell and a high-toughness elemental bamboo fiber core, which solves the brittleness problem of the secondary molded carbon rod and breaks through many technical obstacles in the preparation process of the highly conductive carbon rod.
[0033] (3) The process technology involved in the present invention has a sufficient industrialization foundation. The raw materials are natural bamboo biomass materials that are abundant, sustainable and low-cost. They can be self-formed without the assistance of chemical adhesives and artificial synthetic organic carbon sources. The production equipment is simple and can be automated, which is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 A schematic diagram of a process for preparing highly conductive core-shell carbon rods from natural bamboo provided in a specific embodiment;
[0035] Figure 2 (a) Full spectrum of X-ray photoelectron spectrum, (b) C1s spectrum, element ratio results obtained by characterization, and (c) Raman spectrum data diagram of the highly conductive core-shell carbon rod prepared in Example 2;
[0036] Figure 3 The optical photo, electron microscope photo and resistivity data graph of the highly conductive core-shell carbon rod prepared in Example 6 are shown in FIG. Figure 3 (a) is an optical photograph of a highly conductive core-shell carbon rod. Figure 3 (b) is an electron microscope photo of a highly conductive core-shell carbon rod. Figure 3 (c) is the resistivity data of highly conductive core-shell carbon rods.
[0037] Figure 4 The tensile mechanics curve of the highly conductive core-shell carbon rod prepared in Example 1 DETAILED DESCRIPTION
[0038] In order to enable those skilled in the art to better understand the solutions of the present invention, the following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0039] The present invention will be further described below in conjunction with specific embodiments.
[0040] Embodiment 1:
[0041] 1) Cut three-year-old arrow bamboo into bamboo chips, dry them for 10 days to obtain yellow-brown bamboo chips, cut the bamboo chips into bamboo sticks, and polish them to obtain cylindrical raw materials with a diameter of 2 cm and a length of 20 cm;
[0042] 2) 10 cylindrical raw materials are bundled into a bundle, fixed with a clamp, and the lower 4 cm of the cylindrical raw materials are immersed in 100 ml of 83 wt% phosphoric acid dehydration carbonization reaction solution, and kept warm at 70° C. for 1 hour. After taking out, the clamp is released and the bundle is untied to obtain a low-temperature fast carbonized core-shell carbon rod;
[0043] 3) The reacted core-shell carbon rod was immersed in 2000 ml of deionized water for 12 hours, and the black part was cut off to obtain a highly conductive core-shell carbon rod. The carbon content of the carbon shell of the carbon rod was 88%, the thickness of the carbon shell was 45% of the total diameter, the volume shrinkage was 6%, and the resistivity was 105Ω / cm.
[0044] Embodiment 2:
[0045] 1) Cut three-year-old bamboo into bamboo chips, dry them for 8 days to obtain yellow-brown bamboo chips, cut the bamboo chips into bamboo sticks, and polish them to obtain cylindrical raw materials with a diameter of 3 cm and a length of 20 cm;
[0046] 2) Bundle 15 cylindrical raw materials into a bundle, fix them with a clamp, immerse the lower 5 cm of the cylindrical raw materials in 200 ml of 98 wt% fuming sulfuric acid dehydration carbonization reaction solution, keep warm at 55° C. for 0.5 hour, loosen the clamp and untie the bundle after taking out, and obtain a low-temperature fast carbonized core-shell carbon rod;
[0047] 3) The reacted core-shell carbon rod was immersed in 3000 ml of deionized water for 12 hours, and the black part was cut off to obtain a highly conductive core-shell carbon rod. The carbon content of the carbon shell of the carbon rod was 83%, the thickness of the carbon shell was 55% of the total diameter, the volume shrinkage was 8%, and the resistivity was 50Ω / cm.
[0048] Embodiment 3:
[0049] 1) Cutting down 5-year-old bamboos into bamboo chips, drying them in the sun for 10 days to obtain yellow-brown bamboo chips, cutting the bamboo chips into bamboo sticks, and polishing them to obtain cylindrical raw materials with a diameter of 5 cm and a length of 30 cm;
[0050] 2) Bundle 20 cylindrical raw materials into a bundle, fix them with a clamp, immerse the lower 10 cm of the cylindrical raw materials in 400 ml of a 60wt% phosphoric acid / 64wt% oleum mixed dehydration carbonization reaction solution, keep warm at 55°C for 2 hours, loosen the clamp and untie the bundle after taking out, and obtain a low-temperature fast carbonized core-shell carbon rod;
[0051] 3) The reacted core-shell carbon rod was immersed in 3000 ml of deionized water for 10 hours, and the black part was cut off to obtain a highly conductive core-shell carbon rod. The carbon content of the carbon shell of the carbon rod was 82%, the thickness of the carbon shell was 50% of the total diameter, the volume shrinkage was 3%, and the resistivity was 210Ω / cm.
[0052] Embodiment 4:
[0053] 1) Cut 4-year-old phoenix tail bamboo into bamboo chips, dry them for 5 days to obtain yellow-brown bamboo chips, cut the bamboo chips into bamboo sticks, and polish them to obtain cylindrical raw materials with a diameter of 2 cm and a length of 10 cm;
[0054] 2) Bundle the 5 cylindrical raw materials into a bundle, fix them with a clamp, immerse the lower 2 cm of the cylindrical raw materials in 50 ml of a 40 wt% hydrochloric acid / 20 wt% phosphorus pentoxide mixed dehydration carbonization reaction solution, keep the mixture at 95° C. for 4 hours, loosen the clamp and untie the bundle after taking them out, and obtain a low-temperature fast carbonized core-shell carbon rod;
[0055] 3) The reacted core-shell carbon rod was immersed in 500 ml of deionized water for 5 hours, and the black part was cut off to obtain a highly conductive core-shell carbon rod. The carbon content of the carbon shell of the carbon rod was 80%, the thickness of the carbon shell was 40% of the total diameter, the volume shrinkage was 2%, and the resistivity was 380Ω / cm.
[0056] Embodiment 5:
[0057] 1) Cut three-year-old mottled bamboos into bamboo chips, dry them for 10 days to obtain yellow-brown bamboo chips, cut the bamboo chips into bamboo sticks, and polish them to obtain cylindrical raw materials with a diameter of 5 cm and a length of 10 cm;
[0058] 2) Bundle 20 cylindrical raw materials into a bundle, fix them with a clamp, immerse the lower 5 cm of the cylindrical raw materials in 600 ml of 64 wt% oleum / 30 wt% sodium nitrate mixed dehydration carbonization reaction solution, keep warm at 65° C. for 2 hours, loosen the clamp and untie the bundle after taking out, and obtain a low-temperature fast carbonized core-shell carbon rod;
[0059] 3) The reacted core-shell carbon rod was immersed in 1500 ml of deionized water for 10 hours, and the black part was cut off to obtain a highly conductive core-shell carbon rod. The carbon content of the carbon shell of the carbon rod was 86%, the thickness of the carbon shell was 65% of the total diameter, the volume shrinkage was 5%, and the resistivity was 80Ω / cm.
[0060] Embodiment 6:
[0061] 1) Cut three-year-old water bamboo into bamboo chips, dry them for 6 days to obtain yellow-brown bamboo chips, cut the bamboo chips into bamboo sticks, and polish them to obtain cylindrical raw materials with a diameter of 0.5 cm and a length of 10 cm;
[0062] 2) Bundle 20 cylindrical raw materials into a bundle, fix them with a clamp, immerse 1 cm of the lower part of the cylindrical raw materials in 200 ml of 40 wt% phosphoric acid / 10 wt% citric acid mixed dehydration carbonization reaction solution, keep warm at 75° C. for 4 hours, loosen the clamp and untie the bundle after taking out, and obtain a low-temperature fast carbonized core-shell carbon rod;
[0063] 3) The reacted core-shell carbon rod was immersed in 800 ml of deionized water for 6 hours, and the black part was cut off to obtain a highly conductive core-shell carbon rod. The carbon content of the carbon shell of the carbon rod was 81%, the thickness of the carbon shell was 55% of the total diameter, the volume shrinkage was 1%, and the resistivity was 320Ω / cm.
[0064] Comparative Example 1:
[0065] The parameters different from those in Example 1 are:
[0066] 1) Cut one-year-old arrow bamboo into bamboo slices, dry them for 3 days until they turn green, cut the bamboo slices into bamboo sticks, and polish them to obtain cylindrical raw materials with a diameter of 0.5 cm and a length of 3 cm;
[0067] 2) Without bundling, the carbon rods were directly immersed in 100 ml of 83 wt% phosphoric acid dehydration carbonization reaction solution and kept at 100 °C for 8 hours, and carbon crumbs were obtained instead of core-shell carbon rods;
[0068] 3) The carbon crumbs after the reaction were immersed in 5000 ml of deionized water for 48 hours to obtain carbon powder with a resistivity of up to 3000 Ω / cm.
[0069] Performance Testing:
[0070] The carbon conversion amount, the mass of the converted carbon, the core-shell microstructure and the conductive properties of the highly conductive core-shell carbon rods derived from natural bamboo prepared in Example 1, Example 2, Example 3, Example 4, Example 5 and Example 6 were measured in an X-ray photoelectron spectroscopy system, a laser Raman imaging system, a field emission scanning electron microscope system and a four-probe square resistance test system.
[0071] The results are attached Figure 1 is a flow chart of biomass-derived graphene with controllable number of layers prepared in Example 3, wherein, Figure 1 As shown, natural bamboo sticks are transformed into highly conductive core-shell carbon rod structures after rapid carbonization at low temperature, and the main chemical components and structures of the outer layer of natural bamboo biomass have changed;
[0072] like Figure 2 The X-ray photoelectron spectrum (full spectrum, C 1s fine spectrum, element composition data and chemical bond ratio data) and Raman spectrum of the high conductive core-shell carbon rod from natural bamboo prepared in Example 2 are shown in FIG. Figure 2As shown in a and b, the carbon content of this highly conductive core-shell carbon rod reaches 83%, and the proportion of C=C double bonds is as high as 52.30%. Figure 2 As shown in c, the average data of three test points shows I D / I G The ratio is as low as 0.87, indicating that its carbon quality is high;
[0073] The results are attached Figure 3 The optical photograph, the scanning electron microscope photograph of the cross section and the resistivity data graph of the highly conductive core-shell carbon rod derived from natural bamboo prepared in Example 6 are as follows: Figure 3 As shown in a and b, natural bamboo can be formed into carbon rods in one step under this low-temperature rapid process. The core-shell layered structure can be clearly seen in the cross section, with the bamboo fiber core inside and the carbon shell outside. The electron microscope photo shows the interface distribution of the core-shell more clearly, such as Figure 3 As shown in c, the resistivity of the carbon rod is as low as 50Ω / cm.
[0074] like Figure 4 : is a tensile mechanical curve data diagram of a highly conductive core-shell carbon rod derived from natural bamboo prepared in Example 1, such as Figure 1 As shown, the highly conductive core-shell carbon rod reaches a stress of 562MPa at a strain of 3.7%, and the calculated Young's modulus is as high as 52.4GPa.
[0075] The scanning electron microscope images, spectral data and four-probe data (see the attached manual) Figure 1 , attached Figure 2 , attached Figure 3 and attached Figure 4 As shown, the high-conductivity core-shell carbon rod derived from natural bamboo of the present invention has the characteristics of core-shell structure, good quality, high conductivity and high mechanical strength, and the low-temperature rapid preparation method can save energy by more than 80% and save more than 60% of working hours.
[0076] The above examples are only specific embodiments of the present invention. The present invention is not limited to the above examples, and many variations are possible. All variations that can be directly derived or associated with the contents disclosed by a person skilled in the art should be considered as the protection scope of the present invention.
Claims
1. A method for preparing a highly conductive core-shell carbon rod, characterized in that: include: (1) cutting and polishing bamboo to obtain bamboo raw materials with a diameter of 0.5-5 cm and a length of 10-30 cm; (2) 5-20 bamboo raw materials are bundled and fixed, and the lower part of the fixed bamboo raw materials is immersed in 20-400 mL of dehydrated carbonization reaction liquid, the concentration of the reaction liquid is 10-98%, and the temperature is kept for 0.5-4 hours to obtain a core-shell carbon rod; (3) immersing the core-shell carbon rod in deionized water for at least 2 hours and then drying it, and removing the uncarbonized portion of the dried core-shell carbon rod to obtain a highly conductive core-shell carbon rod; The insulation temperature is 55-95°C.
2. The method for preparing a highly conductive core-shell carbon rod according to claim 1, characterized in that: The bamboos are 3-5 year old bamboos.
3. The method for preparing a highly conductive core-shell carbon rod according to claim 1, characterized in that: The method for preparing the bamboo raw material comprises: The bamboo is cut into bamboo chips, the bamboo chips are air-dried for 5-10 days to form yellow-brown bamboo chips, the yellow-brown bamboo chips are cut into bamboo sticks, and the bamboo sticks are polished to obtain bamboo raw materials.
4. The method for preparing a highly conductive core-shell carbon rod according to claim 1, characterized in that: The bamboo is one of arrow bamboo, spotted bamboo, water bamboo, nan bamboo, arhat bamboo or phoenix tail bamboo.
5. The method for preparing a highly conductive core-shell carbon rod according to claim 1, characterized in that: The fixed bamboo raw material is immersed in the dehydrated carbonization reaction liquid for a length of 1-10 cm.
6. The method for preparing a highly conductive core-shell carbon rod according to claim 1, characterized in that: The reaction solution is one or more of phosphorus pentoxide solution, phosphoric acid solution, fuming sulfuric acid solution, sodium nitrate, hydrochloric acid, and citric acid.
7. The method for preparing a highly conductive core-shell carbon rod according to claim 1, characterized in that: The volume of the deionized water is 200-3000 mL, and the soaking time is 2-12 h.
8. A high-conductivity core-shell carbon rod prepared by the method for preparing a high-conductivity core-shell carbon rod according to any one of claims 1 to 7, characterized in that: The interior of the highly conductive core-shell carbon rod is a bamboo structure, the outer shell is carbon, the carbon content is more than 80%, and the thickness of the outer shell is 40%-65% of the diameter of the highly conductive core-shell carbon rod.
9. The high-conductivity core-shell carbon rod prepared by the method for preparing a high-conductivity core-shell carbon rod according to claim 8, characterized in that: The resistivity of the highly conductive core-shell carbon rod is 50-400Ω / cm.
Citation Information
Patent Citations
Sodium ion battery negative electrode material PTA macroporous layered carbon rod and preparation method thereof
CN114420883A
Double-component quick burning charcoal rod prepared through using bamboo charcoal powder, and preparation method thereof
CN105176621A
Biomass-based carbon electrode material and preparation method and application thereof
CN113979434A